Real Wage Adjustment in the Former Soviet Union - Dicks-Mireaux, Louis (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1993)
Since 1991, the economies of the former Soviet Union have experienced sizeable shocks that have pushed equilibrium real wages far from pre-transition levels. This paper sets out a framework in which to assess the degree of real wage adjustment needed to restore equilibrium, and discusses practical problems in applying wage targets and monitoring real wage developments. A key policy conclusion is that because the accuracy of real wage targets is inevitably suspect, observable indicators should be identified to evaluate the adequacy of actual movements in real wages and of the wage targets; rigid indexation rules should be avoided in nominal incomes policies. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text. Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the author(s) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.